Effect of basal insulin supplement therapy on diabetic retinopathy in short‐duration type 2 diabetes: A one‐year randomized parallel‐group trial. Issue 12 (30th May 2019) - Mu, Pan‐Wei; Tang, Xi‐Xiang; Tan, Ying; Wang, Yi‐Na; Lin, Shuo; Wang, Man‐Man; Shu, Jiong; Wang, Jing; Zhang, Yong‐Jun; Liang, Hua; Lin, Bai‐Run; Cai, Meng‐Yin; et al.
Abstract: Background: In this study, we compared the effect on diabetic retinopathy (DR) between oral antidiabetic drugs (OADs) alone and in combination with basal insulin‐supported OADs therapy (BOT). [Correction added on 11 November 2019, after first online publication: In Abstract under Background section, "DR" has been corrected into "diabetic retinopathy (DR)".] Methods: Between January 2015 and January 2018, this study enrolled 290 patients (age 18‐65 years) with diabetes duration between 0 and 5 years. Patients were randomly assigned to receive OADs or BOT after 14 days intensive insulin treatment. Examinations were performed at the beginning and end of the study. Results: Fewer patients developed DR in the BOT than OADs group (8 [6.06%] vs 12 [8.3%], respectively), and all cases of DR were non‐proliferative. Blood glucose concentrations were higher in the BOT than OADs group at the 3rd month, but lower in the former at the 6th and 12th month. The rate of reaching target HbA1c ≤7% was lower in the BOT than OADs group at the 3rd month (63.6% vs 72.2%, respectively), similar between the two groups at the 6th month (60.6% vs 66.6%, respectively) and higher in the BOT group at the 12th month (75.0% vs 61.1%, respectively). The SD of fasting blood glucose (FBG), coefficient of variation of FBG, SD of blood glucose (SDBG), and mean amplitude of glycemic excursions were lower in the BOT than OADs group. Changes in the levels of three cytokines (interleukin [IL]‐1β, IL‐6, and IL‐17α) were significantly less in the BOT than OADs group. Conclusions: Twelve months of BOT decreased the incidence of DR in short‐duration type 2 diabetes by reducing glycemia more effectively, stably, and completely than OADs alone. Abstract : Highlights This study suggests that basal insulin‐supported oral antidiabetic drugs (OADs) therapy is superior to OADs alone in preventing diabetic retinopathy. This will help clinicians to select a suitable subsequent therapy after initial intensive insulin therapy. 摘要: 背景: 在本研究中, 我们比较单纯口服抗糖尿病药物(oral antidiabetic drugs, OADs)和基础胰岛素联合口服抗糖尿病药物(basal insulin‐supported OADs therapy, BOT)两种治疗方案对糖尿病视网膜病变(diabetic retinopathy, DR)的影响。 方法: 本研究在2015年1月到2018年1月共入组290例糖尿病患者, 他们的年龄介于18到65岁之间, 糖尿病病程在0到5年之间。入组的患者先接受14天的胰岛素强化治疗, 然后被随机分入OAD组或者BOT组。在研究开始时和研究结束时进行相应的检查。 结果: 与OADs组相比, BOT组更少患者出现DR [BOT组8例 (6.60%) vs. OADs组12例 (8.3%)], 并且所有出现DR的患者, 其DR都属于非增殖性病变。BOT组第3个月的血糖水平较OADs组高, 但其第6个月和第12个月的血糖水平则较OADs组低。HbA1c(≤7%)的达标率, 第3个月BOT组低于OADs组(分别为63.6% 和72.2%), 第6个月两组近似(分别为60.6% 和66.6%), 第12个月BOT组高于OADs组(分别为75.0% 和61.1%)。BOT组的空腹血糖标准差、空腹血糖变异系数、血糖标准差和血糖波动平均幅度均低于OADs组。BOT组中三个细胞因子(IL‐1β、IL‐6和IL‐17α)的变化水平显著低于OADs组。 结论: 对于病程较短的2型糖尿病患者, 12个月的BOT方案能通过更有效、平稳、全面地降低血糖而降低DR的发生率。